What's the Meaning of "This''? A Puzzle about Demonstrative Belief - Austin, David F. (Cornell University Press, 2019)
A variety of examples in recent literature on philosophy of mind and language raise serious problems for the traditional analysis of belief (and the other so-called propositional attitudes) as a two-term relation between a believer and a proposition. Because of the attractiveness of the traditional analysis and the absence of a clear alternative, such examples raise genuine puzzles about belief. In this lucid and rigorous book, David F. Austin provides a new test case for any theory of the propositional attitudes. Focusing on a puzzle about beliefs that we express using the demonstratives "this" and "that," Austin shows that a key doctrine in the analytic tradition, the doctrine of propositions, is threatened by inconsistency. The author first explains why the traditional doctrine requires individual propositions to accommodate Kripkean intuitions for direct reference. Austin then formulates a deep puzzle about demonstrative belief, using the book's central example, the Two Tubes case, which involves simultaneous, consistent, occurrent, demonstrative beliefs resulting from direct visual perception. Austin argues that none of the leading propositional theories solves this puzzle, nor do the self-attributive views of Chisholm and Lewis, or Kaplan's three-term view. Austin concludes that although his puzzle remains a puzzle, it gives us reason to supplement, rather than abandon, the use of propositions in analyzing thought, and he sketches a three-term, Russian alternative